Making energy research more responsive: public dialogue as experiment - Mohr, Alison (University of Nottingham, 2014)
The UK Civil Service Reform Plan includes a commitment to embedding systems that are open to a broad range of inputs, including those of the public. Public responsiveness is therefore recognized as a key characteristic of good governance including in the field of science and technology policy-making. Since the influential 2000 ‘Science and Society’ report from the House of Lords Select Committee on Science and Technology, research councils and Government departments have sponsored dialogues around several prospective technologies and associated policy options including the commercialisation of genetically modified crops, stem-cell research, nanotechnology and synthetic biology. In light of the commitment to open policy-making, what, then, are the prospects for public dialogue in making research policy more responsive?